2016
DOI: 10.3389/fpls.2016.00601
|View full text |Cite
|
Sign up to set email alerts
|

Copper Trafficking in Plants and Its Implication on Cell Wall Dynamics

Abstract: In plants, copper (Cu) acts as essential cofactor of numerous proteins. While the definitive number of these so-called cuproproteins is unknown, they perform central functions in plant cells. As micronutrient, a minimal amount of Cu is needed to ensure cellular functions. However, Cu excess may exert in contrast detrimental effects on plant primary production and even survival. Therefore it is essential for a plant to have a strictly controlled Cu homeostasis, an equilibrium that is both tissue and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
145
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 289 publications
(151 citation statements)
references
References 129 publications
(218 reference statements)
2
145
0
4
Order By: Relevance
“…Cu binding to apoproteins in post-Golgi compartments is likely conserved in plants. Cu is transported into and out of endomembrane compartments through AtHMA5, a Cu pump, and other Cu transporters (Blaby-Haas and Merchant, 2014;Printz et al, 2016). Plants possess multicopper oxidases, like extracellular laccases (Turlapati et al, 2011) and apoplastic ascorbate oxidases.…”
Section: Compartment [K + ] Affects Metal Homeostasis In Yeastmentioning
confidence: 99%
“…Cu binding to apoproteins in post-Golgi compartments is likely conserved in plants. Cu is transported into and out of endomembrane compartments through AtHMA5, a Cu pump, and other Cu transporters (Blaby-Haas and Merchant, 2014;Printz et al, 2016). Plants possess multicopper oxidases, like extracellular laccases (Turlapati et al, 2011) and apoplastic ascorbate oxidases.…”
Section: Compartment [K + ] Affects Metal Homeostasis In Yeastmentioning
confidence: 99%
“…In addition to these functions, plants require Cu for the perception of hormones, cell wall dynamics, and response to pathogens and reproduction (Shorrocks and Alloway, 1988;Ravet and Pilon, 2013;Mendel and Kruse, 2012;Printz et al, 2016;Broadley et al, 2012). Cu deficiency in humans is an increasingly recognized cause of anemia (Daughety and DeLoughery, 2017) and the dramatic consequences of imbalanced Cu homeostasis are known as Menkes and Wilson diseases (Llanos and Mercer, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on micronutrient levels required for plant growth have shown that salinity is an important factor in determining micronutrient availability (Richards, 1954). Copper is classified as one of the essential micronutrients in plant nutrition, which acts as a cofactor of numerous enzymes and has a vital role in cellular functions (Printz et al 2016). As a transition metal Cu in plant cells appears in two forms: the reduced Cu + state and the oxidized Cu 2+ state.…”
Section: Introductionmentioning
confidence: 99%